1988
DOI: 10.1016/s0022-5347(17)42880-1
|View full text |Cite
|
Sign up to set email alerts
|

Torulopsis Glabrata Urinary Infections: A Review

Abstract: During a 12-year prospective period 9 referral patients were treated for proved Torulopsis urinary infections. Of the 9 patients 7 had irritative voiding symptoms and pyuria was present in 8. To estimate incidence of infection, a retrospective review was performed between January 1982 and December 1983. A total of 105 urine specimens from 57 hospitalized patients yielded Torulopsis glabrata. Two patients suffered symptomatic invasive infections. Patients were treated with antifungal therapy only when invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…However, because isolation of bacteria in the urine samples was not controlled for, the authors acknowledged that bacteria may have been a possible cause of the pyuria reported. In another small study of Torulopsisglabrata urinary tract infections (UTIs), pyuria was present in eight of nine patients with invasive, symptomatic disease and in only 25 of 55 (45 %) believed to have asymptomatic colonization (5). However, eight of the nine patients with invasive disease had previous bacterial UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…However, because isolation of bacteria in the urine samples was not controlled for, the authors acknowledged that bacteria may have been a possible cause of the pyuria reported. In another small study of Torulopsisglabrata urinary tract infections (UTIs), pyuria was present in eight of nine patients with invasive, symptomatic disease and in only 25 of 55 (45 %) believed to have asymptomatic colonization (5). However, eight of the nine patients with invasive disease had previous bacterial UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Storfer et al [4] reported a slightly higher proportion of isolates due to C. glabrata. Risk factors for C. glabrata UTI are similar to those predisposing to C. albicans infection [15,16]. Non-albicans Candida species are also extremely common and far more prevalent than in other sites of Candida infection (oropharynx and vagina), possibly as a function of urine composition and pH selectivity for nonalbicans species.…”
Section: Microbiologymentioning
confidence: 99%
“…Torulopsis glabrata (also known as C. glabrata) exist as saprophytes in the oral cavity, alimentary canal, respiratory tree, and asymptomatic urinary colonization [11]. Diabetes mellitus, antibiotic therapy, surgery, and obstructive uropathy have been associated with T. glabrata infections of the kidneys and bladder [11,12].…”
Section: Infections Caused By Candida Speciesmentioning
confidence: 99%